Three new flavonoids from the roots of Sophora tonkinensis - Yan, Xiao-Yun; Zhang, Rui; Yang, Ya-Nan; Feng, Zi-Ming; Jiang, Jian-Shuang; Yuan, Xiang; Wang, Dong-Mei; Wang, Guo-Cheng; Zhang, Xu; Zhang, Pei-Cheng (Journal of asian natural products research, 2024)
Three new flavonoids including two isoflavanones sophortones A and B (1 and 2), and one chalcone sophortone C (3) were isolated from the roots of Sophora tonkinensis. Their structures were established by UV, IR, HRESIMS, and NMR data. The absolute configurations of 1 and 2 were determined by electronic circular dichroism (ECD) calculations.